Ethical Issues in the Evolution ofCorporate Governance in China - Tam, On Kit (Journal of business ethics, 2002)
China is establishing its corporate governance structures by emulating the stylized Anglo-American model. However, the country does not yet have the necessary formal and informal institutions, or the financial infrastructure to make these structures work effectively. Corruption, stock market manipulation, tax cheating, fraudulent dealing, all manners of plundering of state assets and the lack protection of shareholders' rights are some of the more conspicuous manifestations of the ethical issues that have emerged in this mismatch. This study shows how these issues arise in the context of the characteristics of country's economic and corporate governance development. It evaluates various potential policy responses that may be implemented to improve governance effectiveness and diminish the damage from those problems.